2011
DOI: 10.1029/2011gc003503
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative constraint on footwall rotations at the 15°45′N oceanic core complex, Mid‐Atlantic Ridge: Implications for oceanic detachment fault processes

Abstract: [1] The subsurface geometry of detachment faults at slow spreading mid-ocean ridges is debated: are they planar features that form and slip at low angles, as often inferred for their continental equivalents, or do they initiate at steep angles and then flatten in response to flexural unloading as displacement proceeds, as predicted in "rolling hinge" conceptual models? An essential difference is that significant rotation of the footwall should occur in the rolling hinge but not the planar fault model. This can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 103 publications
(196 reference statements)
2
70
0
Order By: Relevance
“…304/305 samples). The oceanic gabbro layer formed at slow-spreading ridges is considered to be tilted due to detachment faulting (Garcés and Gee, 2007;Morris et al, 2009;MacLeod et al, 2011), and their present remanence inclinations may not reflect the geomagnetic inclination at the time of remanence acquisition. I obtained the mean VADM of 8.2 ± 2.1 10 22 Am 2 after the anisotropy correction (Selkin et al, 2000); before the correction, the mean was 8.3±2.3 10 22 Am 2 (Table 5).…”
Section: Cooling Rate Effect On Plutonic Paleointensitymentioning
confidence: 99%
“…304/305 samples). The oceanic gabbro layer formed at slow-spreading ridges is considered to be tilted due to detachment faulting (Garcés and Gee, 2007;Morris et al, 2009;MacLeod et al, 2011), and their present remanence inclinations may not reflect the geomagnetic inclination at the time of remanence acquisition. I obtained the mean VADM of 8.2 ± 2.1 10 22 Am 2 after the anisotropy correction (Selkin et al, 2000); before the correction, the mean was 8.3±2.3 10 22 Am 2 (Table 5).…”
Section: Cooling Rate Effect On Plutonic Paleointensitymentioning
confidence: 99%
“…These surfaces represent exposed, now-inactive low-angle fault planes that have been directly responsible for the exhumation of mantle and plutonic lithologies onto the seafloor. Paleomagnetic analyses of OCC footwall sections sampled by scientific ocean drilling along the Mid-Atlantic Ridge91011 have demonstrated that this unroofing is characteristically accommodated by tectonic rotation around ridge-parallel, shallowly plunging axes, consistent with flexural, isostatic rolling-hinge deformation1213.…”
mentioning
confidence: 99%
“…Hydrothermal systems hosted by this formation could be related to the alteration of the gabbroic core and/or serpentinization of interfingered ultramafic formations (Andreani et al, 2014;McCaig et al, 2010;Blackman et al, 2014). The origin and extent of possible hydrothermal circulation processes in the subsurface of OCCs and their exact fluid pathways have been discussed extensively in previous studies; yet, the direct evidence remains very sparse except for fluid seepage found from seafloor observations (Andreani et al, 2014;Delacour et al, 2008aDelacour et al, , 2008bEscartín et al, 2008;Früh-Green et al, 2003;Karson et al, 2006;Kelley et al, 2001Kelley et al, , 2005Ludwig et al, 2006Ludwig et al, , 2011Macleod et al, 2011;Tucholke et al, 2013). It has been observed that nearly all ultramafic and gabbroic rocks recovered from the upper 800 m of IODP Hole U1309D on the Central Dome, located in close proximity to our prevalent lithified carbonate crust at Argo II track A39 (Fig.…”
Section: Discussionmentioning
confidence: 94%